Examining the relationships among core self-evaluations, pay preferences, and job satisfaction in an occupational environment - Sovern, Heather S. (Kansas State University, 2008)
A structural equations model hypothesizing that individuals' core self-evaluations would significantly predict their preferences for various pay plan characteristics (e.g., high risk, variable pay, etc.) was tested. This hypothesis, which specified that individuals with higher levels of core self-evaluations would prefer pay plans that offered greater risk and less certainty regarding the amount of pay received, was supported. Furthermore, it was also hypothesized that congruence between an individual's preferred pay plan characteristics and the actual type of pay plan that he or she receives would result in higher levels of employee job satisfaction and pay satisfaction. This hypothesis was partially supported, as the relationship between congruence and job satisfaction was significant, while the relationship between congruence and pay satisfaction was not significant. Finally, it was hypothesized that the relationship between congruence and satisfaction would be moderated by the value that the individual places on money. This hypothesis was not supported. The results of this research indicate that personality characteristics may have a significant impact on the type of pay plan that an individual will prefer to receive. Furthermore, this research provides additional support for the belief that high levels of fit between the characteristics of individuals and the characteristics of the organizations for which they work will result in higher levels of employee satisfaction. Finally, the degree of importance that an individual places on money does not appear to alter the relationship between fit and satisfaction. These results have strong implications for businesses that wish to improve employee satisfaction and reduce employee turnover, as well as for individuals who are seeking occupations for which they will best be suited.
Keywords: Core Self-evaluation; Pay Preference; Job Satisfaction; Pay Satisfaction; Psychology, Industrial (0624)